Clinical factors influencing residual subcutaneous tissue after skin-sparing and nipple-sparing mastectomy with immediate breast reconstruction - Turna, Menekse; Caglar, Hale Basak (Frontiers in Oncology, 2025)
BackgroundSkin-sparing mastectomy (SSM) and nipple-sparing mastectomy (NSM) have emerged as increasingly preferred alternatives to traditional mastectomy, largely due to their enhanced cosmetic outcomes and elevated levels of patient satisfaction. Nonetheless, the oncological safety and implications associated with residual breast tissue in these surgical procedures continue to raise significant concerns. The objective of this study is to evaluate the influence of various clinical and surgical factors on residual subcutaneous tissue in patients undergoing SSM and NSM.MethodsThis retrospective cohort study encompassed breast cancer patients who underwent postoperative radiotherapy following SSM and NSM with immediate breast reconstruction from November 2020 to April 2024. Clinical and demographic data, including age, tumor size, axillary staging, molecular subtype, genetic analysis, and surgical details, were systematically collected. Additionally, radiation treatment planning CT scans were assessed to measure residual subcutaneous tissue thickness at multiple anatomical regions. The correlation between residual subcutaneous tissue thickness and clinical factors was subsequently analyzed.ResultsThe median age was 45 years (range, 31-61). Among the total patients, 20 underwent SSM (52.63%), and 18 underwent NSM (47.37%). An acceptable residual subcutaneous tissue distance (≤5 mm) was observed in 21 breasts (55.26%), while 17 breasts (44.74%) did not meet this criterion. Analysis demonstrated a statistically significant but modest positive correlation between RFT thickness and age (r = 0.38, p = 0.02), minimal positive correlation was observed between RFT thickness and clinical tumor size (r = 0.08, p = 0.042). A significant effect of contralateral breast surgery on residual subcutaneous tissue thickness was noted (F = 8.38, p < 0.001). Additionally, the results also revealed a statistically significant inverse correlation between RFT thickness and axillary involvement (r = -0.18, p = 0.005), suggesting that thicker flaps are associated with reduced axillary involvement. There was no significant difference in RFT thickness between NSM and SSM groups (Chi² = 0.47, p = 0.491).ConclusionA significant proportion of patients undergoing SSM and NSM exhibit residual subcutaneous tissue thickness that exceeds acceptable limits, which may vary based on clinical and pathological factors. Further research involving larger cohorts and prospective designs is essential to identify additional contributing factors and optimize indications for postoperative radiotherapy.